MANAJEMEN PENDIDIKAN INKLUSI DI SEKOLAH UMUM : (Studi Kasus di SD Budi Mulia Dua Yogyakarta) - Ramadhan, Andriawan Fajar; Maryani, Ika (JPI (Jurnal Pendidikan Inklusi), 2024)
A common problem encountered in implementing inclusive classes is the difficulty of class management to meet the needs of children with special needs. The impact of this problem has caused several schools to reject students with special needs on the grounds of limited abilities. This study aims to describe the implementation of inclusive school education management. This study uses a qualitative descriptive approach. This study was conducted in July 2023. The research instrument was in the form of an interview sheet with resource persons, class teachers, inclusive teacher managers, and child psychologists. The results of this study are that inclusive school management can be implemented in various aspects. The first aspect is inclusive school equipment which includes assessments of inclusive students, teachers, and learning aids. The second aspect is classroom arrangement which includes seating arrangements, activities, and learning aids in the classroom. The third aspect is the teacher's duties which include the duties of the class teacher as a facilitator, the assistant teacher as a companion to the class teacher in carrying out learning activities in the classroom, and the inclusive teacher whose job is to accompany inclusive students directly. The last aspect is the obstacles and solutions which include the number of students being educated, intimidatio, and how to prevent it, as well as parents who need objective assessments not only from one point of view regarding inclusive children.